Exploration of ChatGPT Used and Students Critical Thinking Skills in History Learning at SMAN 2 Sidoarjo - Talitha Berly Dahayu; Sri Mastuti Purwaningsih (Journal of Innovative and Creativity, 2025)
The massive use of ChatGPT by students can certainly raise concerns, especially regarding critical thinking skills. ChatGPT tends to provide answers instantly without requiring users to think deeply. The purpose of this research is to explore the use of ChatGPT, the reasons for using it, and whether ChatGPT is able to encourage students' critical thinking skills in history learning. The type of research used is a qualitative method with a case study approach in one school, namely SMAN 2 Sidoarjo. The subjects studied were 38 students in class X. Data was collected through interviews with teachers and students, observations, and documentation in the form of prompts submitted by students on ChatGPT. The data analysis technique used is the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The research results show that students use ChatGPT as a tool in finding historical information, especially in completing assignments, summarizing material, and understanding history. The reason is because ChatGPT is popular among students, the accessibility of ChatGPT is relatively easy or user friendly, and the responses provided are complete. Students critical thinking cognitive abilities stop at the remembering (C1) and understanding (C2) stages, while the disposition of students' critical thinking abilities varies, namely not critical, basic critical, and intermediate critical. No one has yet achieved complex critical thinking, so it is concluded that ChatGPT can encourage students' critical thinking skills even though its use has not been optimized as an exploratory tool. Keywords: ChatGPT, Critical Thinking, History Learning